Geo I -Store: the enhancement of instrument apps for geomatics students / Zailin Mohd Asri - Mohd Asri, Zailin (2023)
Mobile development continues to be a highly demanding field due to the increasing reliance on smartphones and mobile applications in our daily lives. Meanwhile, most the features of the mobile application develop currently are not focused on the geomatics elements. Thus, this study is aimed to enhance the Geo I -Store application to be more efficient and user friendly to students for College of Built Environment in UiTM Perlis branch. In order to accomplish this goal, there are three specific objectives. The initial objective is to determine the strength and weakness of the application. The second objective to produce additional function to improvise the application. Lastly, the third objective is to evaluate the satisfactory of the application among staff and student. Therefore, planning and analysis of the methodology needs to be improved followed by the second phase which is data collection and designing the new features. Thus the result shows that it is proven that the demand of the research is increasing on our geomatics perspective. With this application it can make students ease to borrowing or returning equipment at storeroom.